Downregulation of sperm-associated antigen 5 inhibits melanoma progression by regulating forkhead box protein M1/A disintegrin and metalloproteinase 17/NOTCH1 signaling. Issue 3 (1st March 2022) - Dang, Lin; Shi, Cuiping; Zhang, Qianqian; Liao, Peiyu; Wang, Yan
ABSTRACT: Sperm-associated antigen 5 (SPAG5) has been identified as a driver in several type of cancers. In this study, we aimed to reveal the role of SPAG5 in melanoma and clarify whether FOXM1 (forkhead box protein M1) /ADAM17 (A disintegrin and metalloproteinase 17) /NOTCH1 signaling was involved. The expression of SPAG5 in malignant melanoma (MM) tissues and matched normal tissues was detected using qRT-PCR, immunohistochemistry and Western blotting. Cell viability was tested using CCK-8 (Cell Count Kit-8), colony formation and EdU staining. Cell migration and epithelial to mesenchymal transition (EMT) were measured using transwell chambers and immunofluorescent staining. Cell cycle distribution and tumorigenesis were assessed by flow cytometry and in vivo tumor-bearing experiments, respectively. The results demonstrated that the expression of SPAG5 was increased in MM tissues and cells. Downregulation of SPAG5 inhibited cell viability, migration, invasion and EMT, and induced a G1-phase arrest. In addition, downregulation of SPAG5 decreased the expression of FOXM1, thereafter inhibiting the expression of ADAM17, NOTCH1 and HES1. Furthermore, deletion of SPAG5 expression decreased the tumorigenesis of MM A375 cells. In conclusion, this study demonstrated that SPAG5 was overexpressed in MM. Downregulation of SPAG5 repressed MM cell growth and EMT, which might be induced by inactivation of the FOXM1/ADAM17/NOTCH1 signaling. Graphical abstract: uf0001